Neuroprotective role of sialic-acid-binding immunoglobulin-like lectin-11 in humanized transgenic mice - Abou Assale, Tawfik; Afrang, Negin; Wissfeld, Jannis; Cuevas-Rios, German; Klaus, Christine; Linnartz-Gerlach, Bettina; Neumann, Harald (Frontiers in Neuroscience, 2024)
Brain aging is a chronic process linked to inflammation, microglial activation, and oxidative damage, which can ultimately lead to neuronal loss. Sialic acid-binding immunoglobulin-like lectin-11 (SIGLEC-11) is a human lineage-specific microglial cell surface receptor that recognizes α-2-8-linked oligo−/polysialylated glycomolecules with inhibitory effects on the microglial inflammatory pathways. Recently, the SIGLEC11 gene locus was prioritized as a top tier microglial gene with potential causality to Alzheimer’s disease, although its role in inflammation and neurodegeneration remains poorly understood. In this study, aged Siglec-11 transgenic (tg) mice, which expressed the human SIGLEC-11 receptor on microglia and tissue macrophages, were investigated. The brains of the Siglec-11 tg mice were analyzed in 6-month-old mature mice and 24-month-old aged mice using immunohistochemistry and transcriptomics. Results showed decreased density and fewer clusters of ionized calcium binding adaptor molecule 1 (Iba1)-positive microglial cells in the hippocampus and substantia nigra, as well as less lipid-laden microglia in the Siglec-11 tg in comparison to wildtype (WT) controls. Additionally, Siglec-11 tg mice exhibited less age-related neuronal loss in the substantia nigra pars compacta in comparison to WT mice. Transcriptome analysis revealed suppression of oxidative phosphorylation and inflammatory pathways in Siglec-11 tg brains at 6 months, with further suppression of complement and coagulation cascades at 24 months of age in comparison to WT mice. Gene transcript levels of the pro-inflammatory cytokines tumor necrosis factor alpha (Tnf) and interleukin 1 beta (Il-1β) as well as the oxidative stress markers cytochrome b-245 alpha and beta (Cyba and Cybb) and the nitric oxide synthase 2 (Nos2), were reduced in the brains of 24-month-old Siglec-11 tg mice relative to WT controls. Brains of 24-month-old Siglec-11 tg mice also exhibited lower gene transcription of complement components 3, 4, and integrin alpha M (C3, C4, and Itgam), along with the complement C1q subcomponents a-c (C1qa, C1qb, and C1qc). In summary, aged Siglec-11 tg mice displayed reduced brain inflammation and oxidative stress, as well as protection against age-related neuronal loss in the substantia nigra.